Peningkatan Kompetensi Guru Memanfaatkan Media Pembelajaran Berbasis IT melalui IHT di Sekolah Dasar - Jasmiati Jasmiati (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2019)
School Action Research is intended to improve the ability of teachers to use Information Technology-Based Learning Media. The study was conducted at Sekolah Dasar Negeri 05 Gunuang Malintang with 12 subjects. The data collected through observation, interviews, and tests indicated that the ability to utilize IT-based learning media can be improved through In House Training (IHT). The steps of IHT activities are as follows: (1) Share the initial test with the teacher, (2) The teacher works on the initial test to determine the ability to use and utilize IT as a learning medium. (5) Provide material perceptions about the use of IT-based learning media. (6. Provide services and guidance to teachers about the use of IT. (7) Providing opportunities for teachers to create and innovate in utilizing IT as a learning media. (8) Provide services and guidance to teachers during IHT. (9) Give the final test.